Comparative Test and Analysis of Falling-Ball Instrument and FWD Deflection Detection Method. Issue 2 (May 2020) - Zhang, Chunxia; He, Huayang; Xue, Yingqi; Luo, Zhu
Abstract: Through the experiment, the deflection detection methods of the falling-ball instrument and the falling weight deflect meter (FWD) were compared, and their correlations were analyzed. The results show that the test depth and range of FWD are larger than the falling-ball instrument, and there is a good linear relationship between the road surface deflection values measured by the falling-ball instrument and FWD.